(Invited) Advances in Proton Ceramic Fuel Cells, Steam Electrolyzers, and Dehydrogenation Reactors Based on Materials and Process Optimizations. (31st August 2017) - Norby, Truls
Abstract : Y-doped BaZrO3 -based perovskites form basis for proton ceramic fuel cells (PCFCs) with superior fuel utilization. Likewise, proton ceramic electrolyzers (PCEs) produce directly dry hydrogen at the balanced total pressure of the electrolyzer, while oxygen is diluted with the feed of steam, decreasing the hazard of pure pressurized oxygen. The use of waste or renewable heat to generate and superheat the steam allows operation at high electrical efficiencies. High steam pressures reduce p-type electronic conduction at the oxygen+steam electrode and the use of novel mixed proton-electron conducting double perovskites lowers the overpotential and hence p-type short circuit current further, altogether yielding acceptable faradaic efficiencies of the electrolyzer. Proton conducting ceramics also offer unique opportunities for dehydrogenation of hydrocarbons along different schemes and for different products. With materials and reactor design optimizations as well as process adaptions we now see emerging demonstrations of such use of proton conducting ceramics.